The medical science fiction of James White: Inside and Outside Sector General. Issue 4 (13th September 2016) - Howard, Richard
Abstract : James White was a Northern Irish science fiction author working in the subgenre of medical science fiction from the mid-1950s to the end of the twentieth century. The aim of this article is to introduce White to scholars working in the medical humanities, pointing to features of interest and critiquing the more excessive utopian impulses of the author. The article covers White's Sector General series, set on a vast intergalactic hospital, as well as the author's standalone fictions.